PENGARUH HARGA, LOYALITAS MEREK, KEPERCAYAAN DAN PROMOSI TERHADAP KEPUTUSAN PERPINDAHAN MEREK PADA KONSUMEN KARTU SELULER TELKOMSEL - Hartono Satria Medari, Suprihatmi Sri Wardiningsih & Erni Widajanti (Universitas Slamet Riyadi, 2017)
The development of cellular operators in Indonesia over the last three years(2013-2015) has developed very well. Cellular operator in Indonesia is currentlydominated by three operators, namely Telkomsel, XL Axiata and Indosat. Given theincreasingly intense competition in the pace of today's business world as well as themarket conditions are more uncertain and may change at any time, on the other handconsumers remain free to make his choice will be a brand. Telkomsel as the marketleader telecommunications company, it is necessary to improve the competitive strategy,so it is expected to reduce the occurrence of displacement behavior of customers atTelkomsel users that are likely to occur. The purpose of this study was to analyze thesignificance of the effect of price, brand loyalty, trust and promotion of brand switchingdecisions on consumer mobile cards Telkomsel Faculty of Economics, University ofSlamet Riyadi Surakarta. The population in this study Faculty of Economics 2013-2016Unisri Surakarta force ever used a mobile card products Telkomsel, with an unknownnumber. The number of samples in this study were 100 students, with the samplingtechnique used purposive sampling. Data collection methods used: questionnaire,observation and documentation. Data analysis technique used to test the validity,reliability test, classic assumption test and multiple linear regression analysis. Inconclusion: 1) The influence of price on brand switching decision obtained positiveresults and significant. 2) The effect of brand loyalty to the brand switching decision andsigifikan obtained negative results. 3) Effect of trust in the brand switching decisionresults obtained negative and significant. 4) The effect of promotions on brand switchingdecision results obtained negative and significant.Keywords: price, brand loyalty, trust, promotions, brand switching decision.